New Approaches to Treat Osteoarthritis with Mesenchymal Stem Cells - Kiran Shah; Ashley G. Zhao; Huseyin Sumer (Stem Cells International)
Osteoarthritis is one of the most common chronic health problems in the world that causes disability and chronic pain with reduced mobility and is a progressive degenerative disease in weight-bearing joints such as the knee. The pathology of the joint resulting from OA includes loss of cartilage volume and cartilage lesions leading to inflammation of the articular joint structures; its incidence and progression are associated with a variety of risk factors. Most of the current treatments focus on symptom management such as physical and occupational therapies, pharmacological intervention for pain management, and surgical intervention with limited success and do not address nor halt the progression of the disease. In this review, we will describe the current treatment options for OA and the exciting new translational medical research currently underway utilising mesenchymal stem cells for OA therapy.